Implementation of of Ethnomathematics-Based LKPD Using a Project-Based Model on the Numeracy Skills of Students at SMPN 12 Singkawang - Enjelia, Enjelia; Husna, Nurul; Mariyam, Mariyam; Waridah, Waridah (STKIP Singkawang, 2026)
Numeracy skills are a basic skill students need in everyday life to solve problems. However, the level of numeracy skills among students in Indonesia is relatively low. This study aims to: (1) Determine whether the numeracy skills of students who use ethnomathematics-based worksheets with a project-based learning model are better than those of students who use direct learning at SMP Negeri 12 Singkawang; (2) To determine the difference in student learning independence after using ethnomathematics-based worksheets using a project-based learning model compared to students who use direct learning at SMP Negeri 12 Singkawang. This research is quantitative in nature, using a quasi-experimental design with a post-test only control group. The population in this study was grade VII, consisting of classes VIIa, VIIb, VIIc, VIId, and VIIe, with a total of 155 students. Sampling in this study used purposive sampling. Data collection techniques used test sheets and student learning independence questionnaires. The data analysis techniques used were the independent sample t-test and Mann-Whitney U test. The results of the study were as follows: (1) The numeracy skills of students who used ethnomathematics-based LKPD using a project-based learning model were better than those of students who used a direct learning model; (2) there was a difference in the independence of students who used ethnomathematics-based LKPD using a project-based learning model and students who used a direct learning model with student learning independence in the experimental class being better than in the control class. Penerapan LKPD Bernuansa Etnomatematika Menggunakan Model Berbasis Proyek Terhadap Kemampuan Numerasi Siswa SMPN 12 SingkawangABSTRAKKemampuan numerasi merupakan kemampuan dasar siswa yang dibutuhkan dalam kehidupan sehari-hari untuk dapat memecahkan masalah. Namun tingkat kemampuan numerasi siswa di Indonesiamasih rendah. oleh karena itu, penelitian ini bertujuan untuk; (1) Untuk mengetahui apakah kemampuan numerasi siswa yang menggunakan LKPD bernuanasa etnomatematika dengan model pembelajaran berbasis proyek lebih baik dari pada siswa yang menggunakan pembelajaran langsung di SMP Negeri 12 Singkawang; (2) Untuk mengetahui perbedaan kemandirian belajar siswa setelah menggunakan LKPD bernuansakan etnomatematika menggunakan model pembelajaran berbasis proyek dengan siswa yang menggunakan pembelajaran langsung di SMP Negeri 12 Singkawang. Jenis penelitian ini kuantitatif dengan jenis Quasy Experimental Design dengan desain penelitian Post-test Only Control Group. Populasi dalam penelitian ini adalah kelas VII yang terdiri dari VIIa, VIIb, VIIc, VIId, dan VIIe yang berjumlah keseluruhan 155 siswa. Pengambilan sampel dalam penelitian ini menggunakan purposive sampling. Teknik pengumpulan data menggunakan tes numerasi dan angket kemandirian belajar siswa. Teknik analisis data yang digunakan adalah uji independent sample t test dan man whiteney U test. Hasil penelitian yang diperoleh; (1) Kemampuan Numerasi siswa yang menggunakan LKPD bernuansa etnomatematika menggunakan model pembelajaran berbasis proyek lebih baik dari pada siswa yang menggunakan model pembelajaran langsung; (2) terdapat perbedaan kemandirian belajar siswa menggunakan LKPD bernuansa etnomatematika menggunakan pembelajaran berbasis proyek dengan siswa yang menggunakan model pembelajaran langsung dengan kemandirian belajar siswa pada kelas eksperimen lebih baik dari pada kelas kontrol.Kata Kunci :Model PjBL; Etnomatematika; kemampuan Numerasi; Bentuk Aljabar